Fully Integrated Memristor and Its Application on the Scroll-Controllable Hyperchaotic System - Jie Jin; Li Cui (Complexity)
In this paper, a fully integrated memristor emulator using operational amplifiers (OAs) and analog multipliers is simulated. Based on the fully integrated memristor, a scroll-controllable hyperchaotic system is presented. By controlling the nonlinear function with programmable switches, the memristor-based hyperchaotic system achieves controllable scroll numbers. Moreover, the memristor-based hyperchaotic system is fully integrated in one single chip, and it achieves lower supply voltage, lower power dissipation, and smaller chip area. The fully integrated memristor and memristor-based hyperchaotic system are verified with the GlobalFoundries’ 0.18 μm CMOS process using Cadence IC Design Tools. The postlayout simulation results demonstrate that the memristor-based fully integrated hyperchaotic system consumes 90.5 mW from ±2.5 V supply voltage and it takes a compact chip area of 1.8 mm2.